Association between maternal depressive symptoms with child malnutrition or child excess weight - Thais Feres Moreira Lima; Warles Melo Maciel; Monyk Neves de Alencar; Joana Athayde da Silva Cruz; Carolina Abreu de Carvalho; Antônio Augusto Moura da Silva
Abstract Objectives: to verify associations between maternal depressive symptoms with child malnutrition or child excess weight. Methods: prospective study with data from the BRISA prenatal cohort in São Luís, Brazil, obtained from the 22nd to the 25th week of gestation (in 2009 and 2010) and, later, when children were aged 12 to 32 months (in 2010 and 2012). Maternal depressive symptoms were identified using the Center for Epidemiologic Studies Depression Scale (CES-D) and the Edinburgh Postnatal Depression Scale (EPDS). For the excess weight evaluation, BMI z-score for age > +2 was used. For measuring child malnutrition, height z-score for age < -2 was used. The confounding factors were identified using a directed acyclic graph in DAGitty software. Results: we did not find associations between maternal depressive symptoms with child malnutrition or child excess weight. The prevalence of maternal depressive symptoms was 27.6% during gestation and 19.8% in the second or third year of the child's life. The malnutrition rate was 6% and the excess weight rate was 10.9%. Conclusions: no associations between maternal depressive symptoms in prenatal or in the second or third year of the child's life and child malnutrition or excess weight were detected.